2017
DOI: 10.1016/j.marpetgeo.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Time series video analysis of bubble release processes at natural hydrocarbon seeps in the Northern Gulf of Mexico

Abstract: This research quantifies the rate and volume of oil and gas released from two natural seep sites in the Gulf of Mexico: lease blocks GC600 (1200 m depth) and MC118 (850 m depth). Our objectives were to determine variability in release rates and bubble size at five individual vents and to investigate the effects of tidal fluctuations on bubble release. Observations with autonomous video cameras captured the formation of individual bubbles as they were released through partially exposed deposits of gas hydrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 61 publications
7
37
1
Order By: Relevance
“…In the northern GOM, gas seeping from the seafloor quantified by use of video time-lapse cameras (Johansen et al, 2017) and stereoscopic high-speed cameras (Wang et al, 2016) revealed gas bubble volume rates similar to those determined for the TYK in this study. Estimated gas bubble volume flows at four emission sites in the northern GOM ranged between 13 and 300 mL/min (Wang et al, 2016).…”
Section: Amounts Of Hydrocarbons Released At Tyksupporting
confidence: 80%
“…In the northern GOM, gas seeping from the seafloor quantified by use of video time-lapse cameras (Johansen et al, 2017) and stereoscopic high-speed cameras (Wang et al, 2016) revealed gas bubble volume rates similar to those determined for the TYK in this study. Estimated gas bubble volume flows at four emission sites in the northern GOM ranged between 13 and 300 mL/min (Wang et al, 2016).…”
Section: Amounts Of Hydrocarbons Released At Tyksupporting
confidence: 80%
“…• Even if pockmarks corresponds to the seafloor expression of a focused fluid flow (King and MacLean, 1970), oil can emit from discrete sources outwards of the main fluid conduit Gay et al, 2007;Johansen et al, 2017). Moreover, seafloor emission outlets are subjected to spatio-temporal evolution within seafloor seeps features (Gay et al, 2006a).…”
Section: Accuracy Of the Modelmentioning
confidence: 99%
“…Regarding their activities and fluxes, compared with hydrothermal vents that vigorously eject high flux of "focused flow," macro-seeps are less active but efflux similarly focused flow of seep fluids via subsurface channels. Bubbles of methane gas are occasionally visible in water columns, for example, in the Eel River Basin, off northern California [36] and Northern Gulf of Mexico [37]. By contrast, mini-and micro-seeps slowly exhale "diffuse flow" through sediment matrix pores, and the slow flows are virtually invisible and not readily detectable.…”
Section: Migration and Seepage Of Methanementioning
confidence: 99%